Bone marrow mesenchymal stem cell-derived acellular matrix-coated chitosan/silk scaffolds for neural tissue regeneration. Issue 6 (25th January 2017) - Xue, Chengbin; Ren, Hechun; Zhu, Hui; Gu, Xiaokun; Guo, Qi; Zhou, Yi; Huang, Jing; Wang, Shengran; Zha, Guangbin; Gu, Jianhui; Yang, Yumin; Gu, Yun; et al.
Abstract : A novel tissue engineered nerve graft (TENG) was used for the first time to bridge a 60 mm long nerve gap in a dog sciatic nerve and achieved satisfactory results. Abstract : Extracellular/acellular matrix-containing neural scaffolds represent a promising design of a tissue engineered nerve graft (TENG) for peripheral nerve repair. In this study, we engineered a composite neural scaffold by culturing dog bone marrow mesenchymal stem cells (BMSCs) onto the surface of a chitosan/silk fibroin-based scaffold and then exposing the cell culture to decellularization to deposit acellular matrix (ACM) coatings on the scaffold. This natural biomaterial-based, cell-derived ACM-coated neural scaffold, as a novel nerve graft, was used to bridge a 60 mm long nerve gap in a dog sciatic nerve. At 12 months after grafting, behavioral, functional, and histological evaluation indicated that our developed neural scaffold achieved satisfactory regenerative outcomes, which were very close to those achieved by autologous nerve grafts, the accepted golden standard for peripheral nerve repair. Moreover, additional therapeutic benefits produced by the modification of a neural scaffold with BMSC-derived ACM may be associated with the unique neural activity of the ACM, as evidenced by in vitro experimental findings that the ACM significantly enhanced axonal regrowth and Schwann cell proliferation. Our results will provide a further experimental basis for the translation of ACM-containing neural scaffolds into the clinic.